Aplikasi Perakitan Komputer untuk Media Ajar Menggunakan Teknologi Virtual Reality Berbasis Android - Ayu Latifah; Eri Satria; Fajar Shidiq Gimnastiar (Jurnal Algoritma, 2022)
In Vocational High School Education, especially in the field of computers. Computer subject is one of the compulsory subjects while still in vocational high school. Computer material seems difficult to understand and also sometimes students cannot pay close attention when the teacher is practicing because sometimes the lack of available computer tools makes students unable to fully understand practice, making it difficult to catch up on the material that has been taught. One alternative way of learning that can be done is to study independently. From these problems by developing learning media using Virtual Reality Technology, which is a technology that can display things that are close to the reality around us. This is an alternative way for students to learn independently. The completion method used in making this application is the Multimedia Development Life Cycle (MDLC) with stages starting from concept, design, material collecting, assembly, testing, and finally distribution. The results of this study are in the form of educational applications for assembling computers that have features, Virtual Reality menus, materials, settings, about applications, and making applications using the 3D unity engine. With this application, it is hoped that it will make it easier for students in terms of understanding computer assembly using Virtual Reality so that both students and the public are interested in independent learning.